2005
DOI: 10.1002/ffj.1443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the nature and concentration of substrates in aqueous solutions on the solubility of aroma compounds

Abstract: The solubility of nine aroma compounds (acetone, 2-butanone, 2-hexanone, 2-octanone, ethyl acetate, ethyl butanoate, ethyl hexanoate, n-hexanal, and n-hexanol) in both water and various aqueous solutions was measured at 25°C using the mutual solubility method. The aqueous solutions consisted of sucrose, glucose, sorbitol, glycerol, polyethylene glycol 200, or maltodextrins at different concentrations. Aroma solubility in water decreased with increased hydrophobicity. For aroma molecules which have the same num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
(8 reference statements)
1
17
0
1
Order By: Relevance
“…Indeed, comparing data available in the literature such a variation can be found. For example, air/water partition coefficient of ethyl hexanoate at 25°C varied from 0.21 Â 10 À2 (Covarrubias-Cervantes et al, 2005) to 3.01 Â 10 À2 (mean value of Lubbers et al (1993), Langourieux and Crouzet (1994), Jouenne, 1997;Voilley and Lubbers, 1997) corresponding to a 95% variation. The VASK method led to more reliable results than the PRV method as confidence intervals were smaller.…”
Section: Validation Of the Vask Methods For The Determination Of The Amentioning
confidence: 99%
“…Indeed, comparing data available in the literature such a variation can be found. For example, air/water partition coefficient of ethyl hexanoate at 25°C varied from 0.21 Â 10 À2 (Covarrubias-Cervantes et al, 2005) to 3.01 Â 10 À2 (mean value of Lubbers et al (1993), Langourieux and Crouzet (1994), Jouenne, 1997;Voilley and Lubbers, 1997) corresponding to a 95% variation. The VASK method led to more reliable results than the PRV method as confidence intervals were smaller.…”
Section: Validation Of the Vask Methods For The Determination Of The Amentioning
confidence: 99%
“…Interactions between water -the predominant constituent of many foods -non-volatile food ingredients and flavour molecules have been widely studied and are characterised by the hydrophobicity (log P value) and volatility (gas-liquid partitioning coefficient, also known as Henry's law constant, k H ) of the latter (e.g., Philippe et al, 2003;Seuvre, Philippe, Rochard, & Voilley, 2007). The influences of different types of sugars on gas-liquid partitioning and consequently headspace concentration of flavour compounds released from aqueous carbohydrate solutions have been previously reported in the literature (e.g., Covarrubias-Cervantes, Bongard, Champion, & Voilley, 2005;Goubet, Le Quere, & Voilley, 1998;Hollowood, Linforth, & Taylor, 2002;Lubbers & Guichard, 2003;Nahon, Harrison, & Roozen, 2000;Rabe, Krings, & Berger, 2003;Roberts, Elmore, Langley, & Bakker, 1996). However, several earlier studies appear to contradict one another, showing both suppression and enhancement of flavour release in the presence of sucrose and other carbohydrates (e.g., Friel, Linforth, & Taylor, 2000;Hansson, Andersson, & Leufvén, 2001;Philippe et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have similarly reported a decreased flavor release in the presence of carbohydrates and hydrocolloids (Covarrubias-Cervantes, Bongard, Champion, & Voilley, 2005;Nahon, Navarro y Koren, Roozen, & Posthumus, 1998;Philippe et al, 2003). The lower t max value of cis-3-hexenol in the viscous matrix, as well as the very similar I max value compared to water, cannot yet be fully explained but may be related to a shift towards a more hydrophobic character of the aqueous solutions after adding polyols and bulking agents.…”
Section: Influence Of High-viscosity Solutions On Flavor Releasementioning
confidence: 77%